Sauté External Rotation in Beginner and Advanced Ballet Dancers Trained in Different Backgrounds: The Turnout Paradigm. Issue 4 (December 2018) - Picon, Andreja P.; Rodes, Carolina Hart; Bittar, Adriano; Cantergi, Débora; Loss, Jefferson; Sacco, Isabel C. N.
This study compared lower limb external rotation kinematic patterns during sautés in first position in beginners and experienced ballet dancers with various training backgrounds. The ability to attain a perfect turnout is traditionally thought to be a fundamental aspect of classical ballet, and turnout is identified in the literature as one of the leading causes of dance-related injuries and technical limitations among dancers. Twenty-eight ballet dancers of different technical levels and methods (three groups) were assessed. Coefficients of variation (CV), range of motion (ROM), and mean external rotation angles of hip, knee, and ankle in first position sauté were calculated. Differences among groups were tested with ANOVAs (Tukey's post hoc; p < 0.05). The hip mean external rotation values found during the jump were different between both experienced groups from different training backgrounds (p = 0.02). The inexperienced group presented a significantly greater hip external rotation CV compared to the experienced groups (p < 0.001). There were no differences between groups for values of external rotation at the knee and ankle. It is concluded that higher technical level dancers produce lower variability of hip external rotation while performing sauté in first position. Ballet training background also seems to influence the hip external rotation pattern. Moreover, the knee contributes decisively to turnout composition, not only the hip, as expected.